Psoriasis and medical ramifications: A comprehensive analysis based on observational meta-analyses - Zhou, Yun; Zhong, Lixian; Shen, Lianli; Chen, Sisi; Zeng, Qiuting; Lai, Leizhen; Tang, Shaohui (Frontiers in Medicine, 2022)
Purpose: Based on the large number of systematic review and meta-analyses exploring the relationship between psoriasis and various health outcomes, we conducted an umbrella review to assess the strength and evidence for the association between psoriasis and medical end-point ramifications in patients. Methods: We searched related meta-analyses that investigating the links between psoriasis and medical ramifications from three databases. All summary effect sizes, 95%CIs, heterogeneity and small-study effects in the included meta-analyses were recalculated. We assessed the methodological quality of included articles with AMSTAR 2 tool and graded the epidemiologic evidence. Subgroup analysis based on the severity of psoriasis and study design were also performed. Results: A total of 38 articles comprising 85 unique meta-analyses were included in this study. Although 69 outcomes were statistically significant, only 8 outcomes (non- vascular dementia, ulcerative colitis, pediatric dyslipidemia, gestational diabetes, gestational hypertension, fracture, multiple sclerosis, schizophrenia) showed high quality of epidemiological evidence. Conclusion: We found that psoriasis increased the risk of 69 health outcomes and 8 outcomes were graded as high quality of evidence. No evidence was found that psoriasis was beneficial for any medical end-point. However, in order to verify our results, more large-sample, muti-center prospective cohort studies are needed.